The Influence of the Russian Embargo on the Economic Situation of Apple Producers in the Eastern Part of the Masovia Province - Tomasz Kacprzak; Katarzyna Himstedt (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The article concerns the effects of the Russian embargo on apple producers in Poland. Scientific literature is quite poor in this field, mainly information articles in industry literature and media information are available. The literature was reviewed in this respect and two studies (questionnaire and interview) were carried out. The information obtained allowed us to draw conclusions about the very large negative impact of the embargo on the apple market and to learn about its characteristics. New markets do not generate sufficient demand, in 2018 apple prices dropped below production costs, but this does not reflect in a drop in prices in stores, which means that price speculations take place, and the situation is used by realtors. It is necessary to quickly return to the Russian market, because soon it will be unrecoverable for Polish fruit farmers. It is also necessary to put pressure on the European Union's policy, because nowadays it is the Polish farmers who bear its effects to the greatest extent.